PENDAMPINGAN PEMBUATAN LABEL, KEMASAN, DAN DESAIN PADA UMKM PEYEK BU WANTI DESA BONDRANG, SAWOO, PONOROGO - Mukaromah, Muhimmatul; Advani, Risha; Sutrisno, Risma Rahayu; Dinanti, Widi Putri Setya (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2023)
MSMEs ignore the important role of marketing strategy in product adoption in society. One of the elements of MSMEs to further increase the selling value of goods is labels and packaging. The mentoring activity for making packaged goods labels is used to empower quality improvement and increase the selling value of MSMEs. The object of this activity is the business actor Bu Wanti from Bondrang Village, Ponorogo Regency, Sawoo District. Project products are one of the MSME goods in this community. The obstacle faced by MSMEs is the low quality of label and packaging designs on their products, in addition to the lack of infrastructure and supporting facilities for label designs on product packaging. So that when compared to comparable competitor products, MSME partner products are less desirable. The number of goods that can be produced cannot be increased because the UMKM products in the village do not yet have a large market share. This research uses the ABCD (Asset Base Community Development) approach or method. There are 5 steps in this method, namely inculturation, discovery, design, define and reflection. Pre-activity, core activity, and activity evaluation constitute the implementation strategy. The results of the activity include recommendations for using the latest, hygienic, safe and modern packaging available. This is done as a marketing tactic to attract customer attention which has an impact on increasing sales. The output of the activity is in the form of instructions for making packaging labels and ready-to-use designs for these MSME actors.Keywords: ABCD , Label, Accompaniment, Marketing Strategy